Comparing Three Methods for Reducing Psychotropic Use in Older Demented Spanish Care Home Residents. Issue 7 (8th March 2019) - Weeks, William B.; Mishra, Manish K.; Curto, David; Petersen, Curtis L.; Cano, Pedro; Hswen, Yulin; Serra, Silvia Villamarín; Elwyn, Glyn; Godfrey, Marjorie M.; Soro, Pedro Sánchez; Tomás, José Francisco
Abstract : BACKGROUND/OBJECTIVE: In nursing homes across the world, and particularly in Spain, there are concerns that psychotropic medications are being overused. For older Spanish nursing home residents who had dementia, we sought to evaluate the association between applying interventions designed to reduce inappropriate psychotropic medication use and subsequent psychotropic use. DESIGN: Retrospective, propensity score–matched, controlled, patient‐level observational analysis. SETTING: A total of 45 nursing homes in Spain. PARTICIPANTS: A total of 1653 nursing home residents, aged 70 to 99 years, who had dementia and were prescribed an antipsychotic, anxiolytic, or antidepressant medication, 606 of whom received an intervention; the remainder served as propensity score–matched controls. INTERVENTION: Team Rounds, Screening Tool of Older Persons' Prescriptions (STOPP)/Screening Tool to Alert Doctors to Right Treatment (START) criteria, or a Patient Decision Aid. MEASUREMENTS: At 2 and 4 weeks following intervention: change from baseline drug class–specific milligram‐equivalent daily dose (MEDD); at 2 weeks: patient falls and restraint use. RESULTS: Within each intervention/drug‐class cohort, intervention patients and matched controls had similar baseline demographic characteristics, Charlson scores, lengths of admission, and drug class–specific MEDDs. Compared to controls, patients exposed to Team Rounds experienced a 23.3% (95% confidence interval [CI] = 13.9%‐32.8%) reduction in antipsychotic and a 23.1% (95% CI = 18.3%‐28.0%) reduction in anxiolytic MEDDs; those exposed to Patient Decision Aids had a 24.8% (95% CI = 15.6%‐33.9%) reduction in antipsychotic and a 31.8% (95% CI = 25.5%‐38.2%) reduction in anxiolytic MEDDs; and those exposed to STOPP/START application had a 27.7% (95% CI = 22.4%‐33.0%) reduction in antipsychotic and a 39.5% (95% CI = 35.5%‐43.5%) reduction in anxiolytic MEDDs. Intervention‐associated antidepressant MEDD reductions were statistically significant but less dramatic. Interventions were associated with higher rates of medication discontinuation, but not higher rates of deaths, patient falls, or physical restraints. CONCLUSION: We found strong evidence that the interventions we studied were associated with reduced psychotropic use without commensurate harms, suggesting that such interventions should be incorporated into Spanish nursing home care models. Public reporting of psychotropic medication use in Spanish care homes may encourage care homes to regularly monitor psychotropic medication use and implement such instruments. J Am Geriatr Soc, 2019.